Alexander the Great : His Life and His Mysterious Death - Everitt, Anthony (New York Random House, 2019)
"What can we learn from the stunning rise and mysterious death of the ancient world's greatest conqueror? An acclaimed biographer reconstructs the life of Alexander the Great in this magisterial portrait. More than two millennia have passed, but Alexander the Great is still a household name. His life was an adventure story and took him to every corner of the ancient world. His memory and glamour persist, and his
Include Illustrations, Maps and Index
Keywords: Greece -- Generals -- Kings and rulers -- Alexander, the Great, 356 B.C.-323 B.C